Transformasi Fragmen Al-Qur’an dalam Magi: Studi atas Majmu’atul-Munawwar karya KH. Syafiq Munawwar - Siddiq Abdur Rozzaq (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2020)
The Qur’an is uniquely presented in magical culture. Most people who consider the Qur’an was final and systematic, in the magical culture the Qur’an comes with a variety of forms, different arrangements of general habits, and is used for various practical needs. In contrast to the hafiz-oriented paradigm of memorizing and preserving the Qur’an, Majmu’atul-Munawwar offers a magical perspective that transforms fragments of the Qur’an in a unique form. So, how is the quranic fragment transformation in the magical culture of Majmu’atul-Munawwar? This research applies William A. Haviland’s theory. He says that cultural elements transformed into four mechanisms: discovery, diffusion, cultural loss, and acculturation. This research explains that the quranic fragment in the Majmu’atul-Munawwar can be categorized by two: minor and major. The final form of the Quran in the Mushaf Usmani reconstructed in magical culture. Quranic fragment in Majmu’atul-Munawwar shows that the Qur’an always been transformed in different cultural spaces. Therefore the transformation of the Qur’an is a need.